Regionalization of wind-speed data to analyse tree-line wind conditions in the eastern Andes of southern Ecuador - Wagemann, Julia; Thies, Boris; Rollenbeck, Rütger; Peters, Thorsten; Bendix, Jörg (ERDKUNDE, 2015)
This paper presents a method to extrapolate wind-speed data and to calculate wind-speed and dynamic pressure maps for the complex topography of a mountain rainforest area in the tropical Andes of southeastern Ecuador. The spatial differentiation of dynamic wind pressure in this area is claimed to be a major determinant of the altitude of the tree-line ecotone and to affect the tree line’s physiognomy. The paper presents a hybrid method encompassing statistical data analysis using the Weibull distribution and a digital terrain analysis, taking topographical shelter effects into account. The method is used to derive mean and maximum wind-speed and dynamic pressure maps to reveal whether the tree-line ecotone is influenced by direct wind effects. On average, the tree-line ecotone on the eastern slopes shows a clear average depression of 50 m. These slopes are affected by higher dynamic wind stress, so have a more disturbed canopy. These altered vegetation structures may be caused mainly by direct wind effects and to a smaller extent by indirect effects, such as high humidity.